Brief predator sound exposure elicits behavioral and neuronal long-term sensitization in the olfactory system of an insect - Anton, S. (2011)
Modulation of sensitivity to sensory cues by experience is essential for animals to adapt to a changing environment. Sensitization and adaptation to signals of the same modality as a function of experience have been shown in many cases, and some of the neurobiological mechanisms underlying these processes have been described. However, the influence of sensory signals on the sensitivity of a different modality is largely unknown. In males of the noctuid moth, Spodoptera littoralis, the sensitivity to the female-produced sex pheromone increases 24 h after a brief preexposure with pheromone at the behavioral and central nervous level. Here we show that this effect is not confined to the same sensory modality: the sensitivity of olfactory neurons can also be modulated by exposure to a different sensory stimulus, i.e., a pulsed stimulus mimicking echolocating sounds from attacking insectivorous bats. We tested responses of preexposed male moths in a walking bioassay and recorded from neurons in the primary olfactory center, the antennal lobe. We show that brief exposure to a bat call, but not to a behaviorally irrelevant tone, increases the behavioral sensitivity of male moths to sex pheromone 24 h later in the same way as exposure to the sex pheromone itself. The observed behavioral modification is accompanied by an increase in the sensitivity of olfactory neurons in the antennal lobe. Our data provide thus evidence for cross-modal experience-dependent plasticity not only on the behavioral level, but also on the central nervous level, in an insect.